2020
DOI: 10.1093/ehjci/ehaa946.3686
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing rare variant interpretation in inherited arrhythmias through quantitative analysis of 5182 cases from long QT syndrome and Brugada syndrome consortia cohorts and gnomAD population controls

Abstract: Background/Introduction Guidelines for variant interpretation in Mendelian disease set stringent criteria to report a variant as (likely) pathogenic, prioritising control of false positive rate over test sensitivity and diagnostic yield, and require customisation for the specific genetic characteristics of gene-disease dyads. Inherited arrhythmias like long QT syndrome (LQTS) and Brugada syndrome (BrS) are genetically heterogeneous, with missense variants constituting the preponderance of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…18 Five variants had different classifications between the 2 sequencing centers (affecting 7 individuals); manual review using ACMG criteria was used to adjudicate these variants (File S3). In addition, 1838 individuals (8.4%) were not heterozygous for any P/LP variant, but were heterozygous for ≥ 1of 1648 ultrarare VUS (gnomAD allele frequency <2.5e-5 25,30 ; Table S1). Self-reported White and non-White individuals had a similar frequency of P/LP variants (0.52% for White individuals versus 0.62% for non-White individuals, P=0.37).…”
Section: Patient Characteristics and Genotypesmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Five variants had different classifications between the 2 sequencing centers (affecting 7 individuals); manual review using ACMG criteria was used to adjudicate these variants (File S3). In addition, 1838 individuals (8.4%) were not heterozygous for any P/LP variant, but were heterozygous for ≥ 1of 1648 ultrarare VUS (gnomAD allele frequency <2.5e-5 25,30 ; Table S1). Self-reported White and non-White individuals had a similar frequency of P/LP variants (0.52% for White individuals versus 0.62% for non-White individuals, P=0.37).…”
Section: Patient Characteristics and Genotypesmentioning
confidence: 99%
“…For example, all 5 of the variants assigned PS3 at the strong level were present in at least 1 eMERGE-III carrier with an extreme or severe phenotype. The updated BS3 and PS3 criteria, and recently published hotspot criteria for the 3 studied genes, as well, 30 were used to reclassify the 52 variants (Table 2, Table S13). Twelve variants were reclassified: 3 VUS→LB, 7 VUS→LP, 1 VUS→P, and 1 LP→P.…”
Section: Vus and Variant Reclassificationmentioning
confidence: 99%
See 1 more Smart Citation
“…BrS is a cardiac arrhythmia disorder associated with increased risk of sudden death in young adults and characterised by ST-segment elevation in the right precordial leads of the electrocardiogram (ECG) occurring either spontaneously or after challenge with sodium channel blockers like ajmaline 1 . Rare loss-of-function coding variants in SCN5A , encoding the Na v 1.5 sodium channel underlying the cardiac sodium current (I Na ), are found in approximately 20% of European-ancestry BrS cases 2 . Several other genes have been implicated in BrS but were considered to have limited evidence of association by ClinGen re-evaluation and SCN5A remains the only clinically actionable gene 3,4 .…”
Section: Mainmentioning
confidence: 99%
“…[5] An increasing number of studies have demonstrated that several ECG parameters, including heart rate, P wave, QRS wave duration, T wave, PR segment, RP interval, QT interval, and corrected QT (QTc) interval, credibly reflect the cardiac electrophysiology of the heart. [6–8] Moreover, abnormal ECG parameters in general represent abnormal cardiac electrophysiology. [9] For instance, a prolonged P wave interval represents delayed atrial conduction velocity, indicating an increased risk of atrial fibrillation, [10,11] and a prolonged QTc interval represents an increased dispersion of ventricular repolarization, which may induce malignant arrhythmias including ventricular tachycardia/fibrillation (VT/VF) and sudden death.…”
Section: Introductionmentioning
confidence: 99%